2021
DOI: 10.1140/epjc/s10052-021-09791-5
|View full text |Cite
|
Sign up to set email alerts
|

On the inverse hoop conjecture of Hod

Abstract: Recently, Hod has shown that Thorne’s hoop conjecture ($$\frac{C(R)}{4\pi M(r\le R)} \le 1\Rightarrow $$ C ( R ) 4 π M ( r ≤ R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(30 reference statements)
0
1
0
Order By: Relevance
“… Hod [35] has recently shown that the hoop conjecture valid for static black holes does not hold for spinning black holes and he proposed a new and unified "inverse hoop conjecture"[36] valid for spinning as well as static black holes. This new conjecture has been shown[37] to hold for black hole solutions belonging to a variety of extended gravitational theories including of course general relativity.…”
mentioning
confidence: 84%
“… Hod [35] has recently shown that the hoop conjecture valid for static black holes does not hold for spinning black holes and he proposed a new and unified "inverse hoop conjecture"[36] valid for spinning as well as static black holes. This new conjecture has been shown[37] to hold for black hole solutions belonging to a variety of extended gravitational theories including of course general relativity.…”
mentioning
confidence: 84%